Automatic Weather Station Data from the Vestfonna Ice Cap (Uppsala universitet, 2017)
Under IPY4-Kinnvika installerades en automatisk väderstation (AWS) på Vestfonna Ice Caps västsida på Svalbard av en forskargrupp från institutionen för geovetenskaper, Uppsala universitet. I posten ingår data från perioden 1 maj 2007 - 30 april 2009 om lufttemperatur, relativ fuktighet, 4-komponentsstrålning, vindhastighet, vindriktning och lutningsvinkeln (tilt) för strålningsinstrumentets arm. Data har samlats in i entimmarsintervall (2 timmarsintervall för perioden augusti 2007-april 2008, på grund av begränsad lagringskapacitet) med avläsningar varje minut. Mindre luckor finns i posten. Temperaturmätare har inte ventilerats. During IPY4-Kinnvika an Automatic Weather Station (AWS) was installed on the western margin of the Vestfonna Ice Cap, Svalbard by a group from the Department of Earth Sciences, Uppsala University, Sweden. The record includes data from 1 May 2007 – 30 April 2009 on air temperature, relative humidity, 4-component radiation, wind speed, wind direction and inclination (tilt) of the radiation instrument arm. Data are hourly means (2-hourly August 2007-April 2008, due to limited storage capacity) of readings every minute. Minor gaps exist in the record. Temperature sensors are unventilated.